Aqueous solvent effects on the conformational space of tryptamine: structural and electronic analysis - Lobayan, Rosana M. (2013)
The TRA (3-[2-aminoethyl]indole) is an important neurotransmitter with a close structural and chemical similarity to the neurotransmitter serotonin (5-hydroxytryptamine), and to melatonin (5-methoxy-N-acetyltryptamine), which plays a key role in daily human behavior. Moreover, TRA, and other indolic compounds are very efficient antioxidants. In this work the conformational space of TRA was scanned in aqueous solution, simulating the solvent by the polarizable continuum model. Geometry optimizations were performed at B3LYP/6-31+G** level. Electronic distributions were analyzed at a better calculation level, thus improving the basis set (6-311++G**). A topological study based on Bader’s theory (atoms in molecules) and natural bond orbital (NBO) framework was performed. Structural changes found in solution were related with charge delocalization mechanisms, which explained the changes in the conformational relative population in aqueous phase. Solvent effects on molecular electrostatic potential (MEPs) were also quantified and rationalized through charge delocalization mechanisms, thus connecting changes in MEPs with changes in structure, bond polarization, orbital bonding populations, natural charges, and bond topological properties. Moreover, polarizabilities and dipolar moments were calculated. All conformers were taken into account. Our results are the first prediction of TRA polarizabilities. The results reported contribute to the understanding of the structure, stability and reactivity of TRA and other indole derivatives.